Developing "Herd Immunity" in a Civilian Community Through Incorporation of "Just-In-Time" Tourniquet Application Training. Issue 5 (28th August 2019) - Marcus, Cameron; Pontasch, Josef; Duff, Joseph; Khambadkone, Trisha; Fink, Brian; Jones, Corion; Brickman, Kristopher; Rega, Paul
Abstract: Introduction: Herd immunity, a concept normally applied in vaccinated populations, is a preventative measure to determine if a significant portion of a population can protect vulnerable individuals against a certain disease. Like vaccines, tourniquet education can be a form of herd immunity to protect vulnerable individuals in a population and prevent the loss of life from a peripheral hemorrhage. The authors have identified a deficiency in simple, quick, and effective hemorrhage control education. Therefore, to maximize herd immunity, the novel educational platform evaluates the efficacy of "Just-in-Time" (JiT) tourniquet application training. Hypothesis/Problem: The authors hypothesize that the utilization of JiT training will be effective in promoting both competence and confidence for individuals to utilize tourniquets in response to a disaster environment. Methods: This Institutional Review Board-approved study recruited medical students who were trained in hemorrhage control measures at a Level 1 Trauma Center. Tourniquet training sessions were held, and naïve civilians received tourniquet education. The subjects received a five- to ten-minute lesson on indications, contraindications, and application techniques of commercial and improvisational tourniquets. Participants subsequently applied a tourniquet to an instructor's arm to demonstrate proper tourniquet application for a brachial artery hemorrhage. Pre- and post-educational surveys were completed to test participant competency and confidence. Results: Of the 104 subjects who completed the course, 97 had no prior training in hemorrhage control techniques, including commercial and improvisational tourniquet application. The mean pre-test score was 2.27/5.00 and the mean post-test score was 4.38/5.00, P <.001 (n = 97). When queried "How competent would you feel applying a tourniquet (commercial or improvisational) on an individual with a bleeding wound?" 92/97 felt confident (95%), one felt less confident, and four felt no difference in confidence levels (P <.001). Conclusion: Just-in-Time training is an effective method in teaching naïve civilians proper tourniquet application. This platform could serve as an alternative to more extensive training programs and requires less time, costs, and resources. If a significant number of individuals in a local community can effectively apply a tourniquet in a disaster scenario, a "herd immunity" effect could be achieved to control peripheral hemorrhages.